New Plants for Florida: Forage - Richard L. Jones; Mary Duryea; Berry J. Treat (EDIS, 2003)
Forage improvement research at the FAES traces to its earliest days – the first forage grass variety was released in 1892, and the first forage legume variety was released in 1896. By 1915, almost 1700 plant introductions had been tested and evaluated as potential new varieties. This document is part of Circular 1440, a publication of the Florida Agricultural Experiment Station, the Agronomy Department and IFAS Communication Services, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Publication date August 2003. Originally published as a booklet by IFAS Communication Services June 2003.